(untitled) (Editora Impacto Científico, 2025)
Modern contraception represents a crucial advance in the consolidation of women’s sexual and reproductive rights. Implanon®, the etonogestrel subdermal implant, is a long-acting reversible contraceptive method (LARC) that stands out for its efficacy, safety and ease of use. Expected to be incorporated into the Unified Health System (SUS) in 2025, Implanon represents a central strategy in strengthening public reproductive health in Brazil. This chapter aims to analyze, through an integrative literature review, the effects of using Implanon on female reproductive health, exploring its benefits, limitations and clinical and social implications. The research was conducted on national and international databases, with articles published between 2015 and 2024. The results indicate that Implanon is highly effective (>99%), with a low failure rate and a high degree of satisfaction among users, especially when there is adequate counseling. However, adherence can be compromised by adverse effects such as irregular bleeding and mood swings. The introduction of the method into the SUS should be accompanied by health education strategies, training for professionals and respect for patients’ autonomy. We conclude that Implanon is an important tool for promoting sexual and reproductive health, especially in contexts of social vulnerability.